Expression of cellular components in granulomatous inflammatory response in piaractus mesopotamicus model - Manrique, Wilson Gomez [UNESP]; Claudiano, Gustavo da Silva [UNESP]; Castro, Marcello Pardi de [UNESP]; Petrillo, Thalita Regina [UNESP]; Pereira Figueiredo, Mayra Araguaia [UNESP]; Andrade Belo, Marco Antonio de [UNESP]; Quiroga Berdeal, Maria Isabel; Rodini de Moraes, Julieta Engracia [UNESP]; Moraes, Flavio Ruas de [UNESP] (Public Library Science, 2015)
The present study aimed to describe and characterize the cellular components during the evolution of chronic granulomatous inflammation in the teleost fish pacus (P. mesopotamicus) induced by Bacillus Calmette-Guerin (BCG), using S-100, iNOS and cytokeratin antibodies. 50 fish (120 +/- 5.0 g) were anesthetized and 45 inoculated with 20 mu L (40 mg/mL) (2.0 x 10(6) CFU/mg) and five inoculated with saline (0,65%) into muscle tissue in the laterodorsal region. To evaluate the inflammatory process, nine fish inoculated with BCG and one control were sampled in five periods: 3rd, 7th, 14th, 21st and 33rd days post-inoculation (DPI). Immunohistochemical examination showed that the marking with anti-S-100 protein and anti-iNOS antibodies was weak, with a diffuse pattern, between the third and seventh DPI. From the 14th to the 33rd day, the marking became stronger and marked the cytoplasm of the macrophages. Positivity for cytokeratin was initially observed in the 14th DPI, and the stronger immunostaining in the 33rd day, period in which the epithelioid cells were more evident and the granuloma was fully formed. Also after the 14th day, a certain degree of cellular organization was observed, due to the arrangement of the macrophages around the inoculated material, with little evidence of edema. The arrangement of the macrophages around the inoculum, the fibroblasts, the lymphocytes and, in most cases, the presence of melanomacrophages formed the granuloma and kept the inoculum isolated in the 33rd DPI. The present study suggested that the granulomatous experimental model using teleost fish P. mesopotamicus presented a similar response to those observed in mammals, confirming its importance for studies of chronic inflammatory reaction.